Pharmacotherapy Problems in Best Possible Medication History of Hospital Admission in the Elderly - Ivana Marinović; Ivana Samardžić; Slaven Falamić; Vesna Bačić Vrca (MDPI AG, 2022)
Transfer of care is a sensitive process, especially for the elderly. Polypharmacy, potentially inappropriate medications (PIMs), drug-drug interactions (DDIs), and renal risk drugs (RRDs) are important issues in the elderly. The aim of the study was to expand the use of the Best Possible Medication History (BPMH) and to evaluate polypharmacy, PIMs, DDIs, and inappropriately prescribed RRDs on hospital admission, as well as to determine their mutual relationship and association with patients' characteristics. An observational prospective study was conducted at the Internal Medicine Clinic of Clinical Hospital Dubrava. The study included 383 elderly patients. Overall, 49.9% of patients used 5-9 prescription medications and 31.8% used 10 or more medications. EU(7)-PIMs occurred in 80.7% (n = 309) of the participants. In total, 90.6% of participants had ≥1 potential DDI. In total, 43.6% of patients were found to have estimated glomerular filtration rate < 60 mL/min/1.73 m2, of which 64.7% of patients had one or more inappropriately prescribed RRDs. The clinical pharmacist detected a high incidence of polypharmacy, PIMs, DDIs, and inappropriately prescribed RRDs on hospital admission. This study highlights the importance of early detection of pharmacotherapy problems by using the BPMH in order to prevent their circulation during a hospital stay. The positive correlations between polypharmacy, PIMs, DDIs, and inappropriately prescribed RRDs indicate that they are not independent, but rather occur simultaneously.